If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -58 + 35 = x Combine like terms: -58 + 35 = -23 -23 = x Solving -23 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -23 + -1x = x + -1x Combine like terms: x + -1x = 0 -23 + -1x = 0 Add '23' to each side of the equation. -23 + 23 + -1x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + -1x = 0 + 23 -1x = 0 + 23 Combine like terms: 0 + 23 = 23 -1x = 23 Divide each side by '-1'. x = -23 Simplifying x = -23
| 16x=136 | | -161=7(-n-13) | | -(3-10y)= | | 1.5k=-20 | | -7(6x+3)= | | 2-0.75k=0.125+9 | | P-7=-8 | | 10x+45=20x-15 | | Y+8x=17 | | 30=7x+3-4 | | 5(4x-2)+9=2 | | 9x=36d | | (X)+3t-8y= | | n-38=18 | | 13=-2p+5 | | -4p^2=220 | | Z-6=34 | | 8x+36=48+-4x | | 16p=32*19 | | n-38=1 | | 19v-7v=-108 | | x-30=57 | | 1.3a=12 | | -15-(-6)+1= | | -4p^2-2=223 | | 12-9+(-12)-5-9= | | 40-24=2 | | 32*19= | | -12(-11)= | | x=5x+32+5x+32+9x+9x | | (-18)+6+(-1)= | | 5a+13=1-47 |